Journal of Patient-Reported Outcomes - Unni, Elizabeth J .; Chang, Chih-Hung.; Ruseckaite, Rasa.; Feeny, David; Hays, Ronald D.; SpringerLink (Online service) (Cham : Springer International Publishing : Imprint: Springer.)
The Journal of Patient-Reported Outcomes (JPRO) is an international, open-access, multi-disciplinary journal dedicated to advancing the science and practice of patient-reported outcomes (PROs). JPRO publishes high-quality original research, and serves as a leader in the field, providing innovative insights and methodologies with broad cross-disciplinary relevance. JPRO welcomes submissions of original research articles, comprehensive literature reviews, brief communications, commentaries, editorials, and reviews of recent books and software advances relevant to the topics described below. Submissions should demonstrate innovation, employ novel methodologies, or significantly contribute to the advancement of PROs science. Manuscripts reporting results with broad implications across disciplines are particularly encouraged. Note: JPRO generally does not publish case reports, study protocols, or pilot and feasibility studies. The journal uses the ISOQOL Dictionary of Quality of Life and Health Outcomes Measurement definitions of PROs, patient-reported outcome measures (PROMs), and patient-reported experience measures (PREMs).1 Listed below are some examples of the types of papers to be considered for publication in JPRO. Innovative methods of capturing patient perspectives that are directly linked to outcomes relevant to the patient and analyzing: PROs in clinical trials, observational studies, and real-world research designs PROMs and PREMs in clinical practice and/or clinical research Observer-reported outcomes (e.g.: caregivers) and clinician-reported outcome measures in clinical practice and/or clinical research, observational studies and real-world research designs Performance Outcomes and Digital Health Measures that promote health and wellbeing including Artificial Intelligence (AI). Patient, family, community, and public engagement in PRO research. Methods to engage patients, family members, and the public in the process of PRO-related research, policy formulation, and clinical guidelines development, and the evaluation of the effects of such engagement. Novel and innovative, quantitative and qualitative studies, on the development, psychometric evaluation, and application of PROMs and PREMs. This does NOT include simple linguistic validation and psychometric properties studies of already validated PROMs. Studies of the social and behavioral determinants of health using PROMs and PREMs. Reviews of PROMs and PREMs (e.g.: systematic, scoping, etc.) Definitions Patient-Reported Outcomes (PROs) A measurement of any aspect of a patient$1 (Bs health that comes directly from the patient without interpretation of the patient's responses by a physician or anyone else. A distinction can be made between those outcomes for which no other interpretation is valid, such as the rating of symptoms or difficulty in carrying out an activity, and those outcomes where verification is possible. For example, the patient can be a good source of information on limitations in physical function, but if need be, the information reported on could be verified by observed performance. The term Self-reported Outcome (SRO) would better represent this type of construct. Patient Reported Experience Measures (PREMs) Measures related to patient-centered care that cover aspects of the structure and processes of care as experienced by the patient and not interpreted by any other person. Dimensions of the patient experience covered by PREMs include respect for patients$1 (Bvalues and preferences; provision of information, communication and education; coordination of care; involvement of family; emotional support; physical comfort; preparation for discharge, continuity and transitions in care; and access. In the hospital context, PREMs cover aspects of care such as communication and responsiveness of health professionals, cleanliness and quietness of the environment, pain management, and adequacy of discharge information. PREMs are distinct from measures of satisfaction as the latter is strongly affected by expectations and outcomes2. 1. Mayo NE. ISOQOL Dictionary of Quality of Life and Health Outcomes Measurement: Isoqol; 2015. 2. Bull C, Teede H, Watson D, Callander EJ. Selecting and Implementing Patient-Reported Outcome and Experience Measures to Assess Health System Performance. JAMA Health Forum. 2022;3(4):e220326. doi:10.1001/jamahealthforum.2022.0326.s
Keywords: Quality of life; Patient education; Medicine; Quality of Life Research; Patient Education; Clinical Medicine